Sagot :
Answer:
[tex]$ \mbox{\Large $ \frac{1}{2}$ } $[/tex]
Step-by-step explanation:
1.) Convert the two mixed fractions with similar denominators into improper fractions. Subtract the numerators of the two fractions while keeping the denominators the same, and simplify your final answer in lowest terms.
⇒ [tex]$ \mbox{\large $ 3\frac{1}{4} - 2\frac{3}{4} = \frac{(3 \times 4) + 1}{4} - \frac{(2 \times 4) + 3}{4} = \frac{12 + 1}{4} - \frac{8 + 3}{4}$ } $[/tex]
⇒ [tex]$ \mbox{\large $ \frac{12 + 1}{4} - \frac{8 + 3}{4} = \frac{13}{4} - \frac{11}{4} = \frac{13 - 11}{4} = \frac{2}{4} = \bold{\frac{1}{2}}$ } $[/tex]
2.) Therefore, the difference of [tex]3\frac{1}{4}[/tex] and [tex]2\frac{3}{4}[/tex] is [tex]\frac{1}{2}[/tex].
I hope this helps you understand this concept in Mathematics.
Stay safe po.
#CarryOnLearning
#AnswerForTrees